Design of a stacked circularly polarized slot-patch antenna for X-band applications - Pascarella, Francesca; Mugnaini, Sara; Balleri, Alessio; Scarselli, Chiara; Brizi, Danilo; Monorchio, Agostino (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This paper introduces a numerically investigation of a compact stacked Circularly Polarized (CP) slot-patch antenna designed to operate in X-band (8 -12 GHz). The proposed solution features a coaxially fed circular radiating patch etched on a dielectric substrate, which includes two sector notches positioned on opposite sides at a 45° inclination to achieve circular polarization. Two additional dielectric substrates are placed on the top of the radiating patch, with a parasitic passive patch positioned on each, with the aim of enlarging the overall operating bandwidth. The numerical results demonstrated that the configuration is able to cover a 2.2 GHz band, achieving a minimal Axial Ratio (AR) of 1.2 dB and a gain of 7.4 dB at 10 GHz.